2011
DOI: 10.1111/j.1460-9592.2011.03614.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound‐guided subclavian vein cannulation in infants: supraclavicular approach

Abstract: This US-guided supraclavicular approach for SCV puncture is a new possibility for central venous catheterization in small infants, offering all the advantages of SCV cannulation without the risk of 'pinch-off' syndrome. This technique seems valuable for children and infants and quite easy to apply for physicians trained to US guidance punctures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
81
0
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(92 citation statements)
references
References 20 publications
5
81
0
6
Order By: Relevance
“…They studied placement in children aged 26 months to 8 years. In the same year, Rhondali et al (6) described placement in patients weighing <10 kg. Other studies have assessed placement in patients weighting <5 kg (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…They studied placement in children aged 26 months to 8 years. In the same year, Rhondali et al (6) described placement in patients weighing <10 kg. Other studies have assessed placement in patients weighting <5 kg (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, ultrasound-guided cannulation of the deep veins, i.e., the femoral (FeV), subclavian (SBV), internal jugular (IJV), and brachiocephalic (BCV) veins, has also been reported to be safe and relatively easy in pediatric ICUs and NICUs [1-8]. In such deep veins, large-bore polyurethane catheters (3–4 Fr) can be inserted.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a growing number of studies have documented the high rates of success and low rates of complications using ultrasound via the supraclavicular approach to assist in subclavian line placement in both pediatric and adult populations [7,8,[10][11][12]. The largest, a retrospective series by Bertini et al [9], reported 100% success rate in the placement of 77 subclavian and 42 brachiocephalic lines without complications.…”
Section: Discussionmentioning
confidence: 97%
“…More recently, a growing number of adult and pediatric studies have documented the potential use and advantages of point-of-care ultrasound guidance in the cannulation of the subclavian vein (SCV) as well [2][3][4][5][6]. Furthermore, the supraclavicular approach to point-of-care ultrasound-guided SCV cannulation has demonstrated significant advantages with success and safety when compared with the more traditional "blind" infraclavicular approach [7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%